2001
DOI: 10.1103/physrevlett.86.1347
|View full text |Cite
|
Sign up to set email alerts
|

Modified Magnetism at a BuriedCo/PdInterface Resolved with X-Ray Standing Waves

Abstract: Soft x-ray standing waves produced by a multilayer interference substrate add depth sensitivity to magnetic circular dichroism to resolve changes in Co magnetism across a 1 nm distance from the Co center to the Co-on-Pd interface of a Pd/Co/Pd trilayer with an in-plane magnetization. Large enhancements of the number of Co d holes, and of in-plane orbital and spin magnetic moments, are strongly localized at a thin, chemically modified interface layer. These results provide new insight into magnetic anisotropy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…The magnetically distinct regions at AF/F interfaces can be formed due to the proximity effect in various hybrid systems. 20,21 For instance, a photoemission electron microscopy study revealed a chemical change at a Co/ NiO interface. 8 Such proximity effect at F/AF interfaces and sufficiently large t UC has been ignored in the explanation of significantly reduced experimental values of H eb .…”
Section: Soft X-ray Resonant Kerr Rotation Measurement and Simulationmentioning
confidence: 99%
“…The magnetically distinct regions at AF/F interfaces can be formed due to the proximity effect in various hybrid systems. 20,21 For instance, a photoemission electron microscopy study revealed a chemical change at a Co/ NiO interface. 8 Such proximity effect at F/AF interfaces and sufficiently large t UC has been ignored in the explanation of significantly reduced experimental values of H eb .…”
Section: Soft X-ray Resonant Kerr Rotation Measurement and Simulationmentioning
confidence: 99%
“…Resonant hard and soft X-ray techniques have also been used to detect enhanced interfacial moments in layered systems [51,71].…”
Section: Reduced Dimensionalitymentioning
confidence: 99%
“…Soft x-ray Faraday (transmission) and Kerr (reflection) geometry measurements involve forward and specular scattered beams, respectively, and thus provide information averaging over in-plane magnetic and chemical structure. Even so, these techniques can provide depth-resolution with nm and sub-nm resolution in various ways: tuning to a core level of an ultrathin chemical marker layer is one approach [3]; another is to radically alter the skin depth by tuning across a strong L 3 white line [4]; and yet another uses strong interference from interfaces in multilayer films as a tunable depth probe across buried interfaces [5].…”
Section: Introductionmentioning
confidence: 99%